Political Consciousness and Bodily Experience in Pasolini. The Social Theory of a Plebeian Intellectual - Sánchez Madrid, Nuria (Res Publica. Revista de Historia de las Ideas Políticas, 2023)
This paper suggests a reading of Pier Paolo Pasolini’s cultural criticism of capitalist society. First it addresses the sociological survey of contemporary Italian cultural reality that Pasolini displays, to highlight the forms of life and popular expressions it contains for emancipating the subaltern subject from an alien normativity. Second it broaches the dialogue Pasolini opened with Gramsci’s legacy about the present and future of the Pci, taking into account that Pasolini never broke up with the Italian communist party. Yet he claimed to identify in each context which people fulfils the role of the popular and thus requires to be defended. Finally, the last section of the paper displays the “mimesis” of Dante’s political and civil project by Pasolini, who deems this dispositive of cultural criticism might be reloaded at every historic point. The text draws as conclusion that in Pasolini’s view the poet must keep alive the memory of a “force of the past”, as this one is full of future from a social and political standpoint.
Keywords: Pasolini; Social Theory; Gramsci; Capitalism; Bourgeois Culture; Proletarian Culture; Subalternity